GC-IMS identification of early-warning biomarkers and fungal community dynamics during cigar tobacco mold process - Zhang, Ge; Huang, Kuo; Xie, Qiuxuan; Li, Qingchang; Li, Dong; Ye, Changwen; He, Chen; Xi, Hongru; Ding, Wei; Hu, Qingyuan (Frontiers in Microbiology, 2025)
IntroductionMold-derived contamination in cigar tobacco leaves causes severe economic losses and health risks due to mycotoxin production. This study aimed to identify early-warning biomarkers for mold and elucidate their interaction with fungal communities.MethodGas chromatography-ion mobility spectrometry (GC-IMS) combined with high-throughput sequencing was employed to profile volatile organic compounds (VOCs) and fungal communities during artificial molding.ResultsA total of 72 VOCs were detected, with four compounds (2-methyl-1-butanol-M, 2-methyl-1-butanol-D, 2-propanone, and 1-penten-3-ol) identified as early-warning biomarkers through VIP > 1 and P < 0.05, showing 1.31.5-fold increases in early mold stages (MB3). Furthermore, fungal diversity sharply declined post-molding (OTUs reduced by 85.7%), with Aspergillus dominating (>99.45% abundance), and exhibiting strong positive correlations with 1-penten-3-ol (ρ = 0.61) and benzaldehyde-M (ρ = 0.67).DiscussionThese findings provide actionable biomarkers for industrial mold prevention and insights into fungal-VOC interaction, with implications for perishable crop storage.